Joey Pigza swallowed the key - Gantos, Jack. (New York : Square Fish, Farrar Straus Giroux, 2014)
To the constant disappointment of his mother and his teachers, Joey has trouble paying attention or controlling his mood swings when his prescription meds wear off and he starts getting worked up and acting wired.
Includes Go Fish bonus materials.
Keywords: Attention-deficit hyperactivity disorder -- Juvenile fiction; Single-parent families -- Juvenile fiction; Schools -- Juvenile fiction